Parental Upbringing and Peer Interaction of Senior High School Learners - Aguilar, Paul Ezekiel; Asuque, John Rafael; Estioso, Crystal; Padao, Christian Dave; Palamos, Jhonella (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between parental upbringing and peer interaction among senior high school learners. Anchored in Bandura’s Social Learning Theory (1977) and Bowlby’s Attachment Theory (1988), the research explored how parental behaviors influence adolescents’ social development. A descriptive correlational research design was employed, involving 121 senior high school learners from Holy Cross of Mintal in Davao City, selected through stratified sampling. Data were collected using adopted and modified questionnaires from Akhtar et al. (2022), with reliability confirmed through Cronbach’s alpha values of 0.80 and above. Descriptive statistics and Pearson r correlation were used for data analysis. Findings revealed that the level of parental upbringing was high, particularly in terms of support and facilitation of independence, while the quality of parent–child relationship was rated average. Peer interaction was also found to be high, characterized by strong communication and trust and low levels of alienation. A significant positive relationship was identified between parental upbringing and peer interaction (r = 0.263, p = 0.004), indicating that supportive and autonomy-promoting parenting contributes to healthier peer relationships. The study concludes that parental upbringing plays a crucial role in shaping adolescents’ social competence and emotional well-being. It recommends strengthening communication and emotional closeness within families, promoting supportive parenting practices, and encouraging collaborative efforts among students, parents, and teachers. This study aligns with Sustainable Development Goal 3 (Good Health and Well-Being) by emphasizing adolescents’ mental, emotional, and social development. It contributes to socio-economic, educational, and public health sustainability by highlighting the importance of family environments in fostering socially competent and emotionally resilient individuals.
Keywords: Attachment theory; Parental upbringing; Peer interaction; Social development; Social learning theory; Senior high school learners